Neurodevelopmental disorders at Chris Hani Baragwanath Academic Hospital: a 4-year retrospective database review - Sarah Jane Lowick; Sibongile Mbatha (BMJ Paediatrics Open)
Background Developmental paediatrics is a growing field both globally and locally with increasing demand for medical and educational resources.Methods This retrospective, developmental database review is a baseline description of the Chris Hani Baragwanath Academic Hospital neurodevelopmental clinic population, and the service offered over the past 4 years. The population comprises all patients seen at the clinic from May 2020 to December 2024. Outcomes measured were total patient numbers, demographic, clinical and management variables.Results The cohort comprised 1877 patients. An increase in total patient numbers was observed over the past 4 years. The ratio of male to female patients was 3:1. Median age at referral was 48.8 months with an average waiting period of 12 months. The median, mean and age range at first visit were 60, 66 and 5–192 months, respectively. Autism was diagnosed in 37.1%, non-syndromic intellectual disability in 16.6%, a confirmed genetic diagnosis in 11.8% and a ‘likely genetic disorder’ in 18% of patients. 98 different genetic conditions were identified. Comorbidity included cerebral palsy (11.4%), epilepsy (16.1%), hearing (5.2%) and visual impairment (5.5%). Associated behavioural disorders occurred in 52.8% of patients, predominantly attention deficit hyperactivity disorder (ADHD) (30%). At least one medication was prescribed in 58.2% of children. Over 40% of children were either at home or at crèche; 14.0% were attending mainstream school; 10.5% an autism school; 26.3% a special needs school. Of the 841 (44.8%) children in supported schooling, 47.8% were placed after 7 years of age.Conclusions This study provides insights into the regional burden and clinical presentation of neurodevelopmental disorders. Trends in this region reflect broader global patterns, with increasing numbers of children presenting with complex conditions. Greater resources are needed for earlier diagnosis and therapy, access to all tiers of genetic testing and upscaling of inclusive and special needs education.Trial registration number NHRD GP_202510_105.